PENTINGNYA PENERAPAN TEKNIK KOMUNIKASI DALAM MENINGKATKAN PENJUALAN UMKM PADA MOM YULY PUDDING - Rorlen; Virly Marcelin Chandra; Marcya Stevanni (Jurnal Serina Abdimas, 2026)
Micro, small, and medium enterprises (MSMEs) play an important role in supporting national economic growth, particularly through job creation and improving community welfare. However, many MSME actors still face challenges in designing effective communication and marketing strategies to expand their consumer reach. This community service activity focused on one MSME, Mom Yuly Pudding in Sunter, North Jakarta, to help improve business communication skills, digital promotion, and brand image strengthening through the application of Integrated Marketing Communication (IMC) and interpersonal communication concepts. The activity was carried out in three stages, namely observation of the partner’s communication needs, presentation of communication strategies based on the Ethos–Pathos–Logos approach, and evaluation of strategy implementation after the activity. During the implementation, the owner and employees showed enthusiasm throughout the presentation session and were able to understand the application of communication strategies in promotion and customer service. This activity also encouraged the partner to begin developing more consistent promotional content and to adjust communication according to audience characteristics. In addition, communication among employees and interactions with customers became more organized and directed. Overall, this community service activity provided insight into the importance of integrated and sustainable communication strategies in supporting the competitiveness of MSMEs.   ABSTRAK Usaha Mikro, Kecil, dan Menengah (UMKM) berperan penting dalam mendukung pertumbuhan ekonomi nasional, terutama melalui penciptaan lapangan kerja serta peningkatan taraf hidup masyarakat. Namun, masih banyak pelaku UMKM yang mengalami kendala dalam merancang strategi komunikasi dan pemasaran untuk memperluas jangkauan konsumen. Kegiatan pengabdian kepada masyarakat ini difokuskan pada salah satu pelaku UMKM, yaitu Mom Yuly Pudding di Sunter, Jakarta Utara, dengan tujuan membantu meningkatkan kemampuan komunikasi bisnis, promosi digital, serta penguatan citra merek melalui penerapan konsep Integrated Marketing Communication (IMC) dan komunikasi interpersonal. Pelaksanaan kegiatan dilakukan melalui tiga tahapan, yaitu observasi kebutuhan komunikasi mitra, pemaparan strategi komunikasi berbasis pendekatan Ethos–Pathos–Logos, serta evaluasi penerapan strategi setelah kegiatan berlangsung. Dalam pelaksanaannya, pemilik dan karyawan menunjukkan antusiasme selama sesi pemaparan dan mampu memahami penerapan strategi komunikasi dalam promosi maupun pelayanan pelanggan. Kegiatan ini juga mendorong mitra untuk mulai menyusun konten promosi yang lebih konsisten dan menyesuaikan komunikasi dengan karakteristik audiens. Selain itu, komunikasi antarpegawai dan interaksi dengan pelanggan menjadi lebih terarah. Secara keseluruhan, kegiatan pengabdian ini memberikan pemahaman tentang pentingnya strategi komunikasi yang terintegrasi dan berkelanjutan dalam mendukung daya saing UMKM.